Ultrasound parameters to identify and diagnose carpal tunnel syndrome. A review of the literature. Issue 3 (3rd August 2020) - Linehan, Callum; Childs, Jessie; Quinton, Ann E.; Aziz, Aamer
Abstract: Numerous works of literature have assessed the use of ultrasound to detect carpal tunnel syndrome, suggesting various techniques and cut‐off values. Currently, an effective parameter and cut‐off value are still debated. The aim of this review is to determine if these parameters have sufficient rigour to allow their use in clinical practice. Twenty‐one studies using sonographic parameters to identify carpal tunnel syndrome in comparison with electrodiagnostic testing (EDx) were selected for review. Methodological differences were found between studies in the use of EDx criteria, scanning and recruitment protocols, with participant biometrics often not reported. Parameters including the cross‐sectional area of the median nerve at the level of the pisiform bone in addition to the wrist‐to‐forearm difference demonstrated high diagnostic utility for set cut‐off values. Doppler techniques and mobility are promising, and further research is required to understand the effectiveness of these techniques.